-6p-(5p+5)=-8-2(p+12)

Simple and best practice solution for -6p-(5p+5)=-8-2(p+12) equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for -6p-(5p+5)=-8-2(p+12) equation:


Simplifying
-6p + -1(5p + 5) = -8 + -2(p + 12)

Reorder the terms:
-6p + -1(5 + 5p) = -8 + -2(p + 12)
-6p + (5 * -1 + 5p * -1) = -8 + -2(p + 12)
-6p + (-5 + -5p) = -8 + -2(p + 12)

Reorder the terms:
-5 + -6p + -5p = -8 + -2(p + 12)

Combine like terms: -6p + -5p = -11p
-5 + -11p = -8 + -2(p + 12)

Reorder the terms:
-5 + -11p = -8 + -2(12 + p)
-5 + -11p = -8 + (12 * -2 + p * -2)
-5 + -11p = -8 + (-24 + -2p)

Combine like terms: -8 + -24 = -32
-5 + -11p = -32 + -2p

Solving
-5 + -11p = -32 + -2p

Solving for variable 'p'.

Move all terms containing p to the left, all other terms to the right.

Add '2p' to each side of the equation.
-5 + -11p + 2p = -32 + -2p + 2p

Combine like terms: -11p + 2p = -9p
-5 + -9p = -32 + -2p + 2p

Combine like terms: -2p + 2p = 0
-5 + -9p = -32 + 0
-5 + -9p = -32

Add '5' to each side of the equation.
-5 + 5 + -9p = -32 + 5

Combine like terms: -5 + 5 = 0
0 + -9p = -32 + 5
-9p = -32 + 5

Combine like terms: -32 + 5 = -27
-9p = -27

Divide each side by '-9'.
p = 3

Simplifying
p = 3

See similar equations:

| f(x+5)=4x+5 | | -32+29= | | A-w=-10 | | 6(x-1)+16(2x+3)=(2x-7) | | -2+x=-x++2 | | 17x+13y=20 | | ydx-(2x+3y)dy=0 | | c=3.14x | | 16-8R-4r+4=24 | | 0=-16t^2+45t+2.5 | | 15x^4-180x^2=0 | | 3x-3=x+2y | | y=7.1x+5.4 | | 4.5+6.8=10.1a-9.1a+3.2 | | 6n=4n+15 | | y=7.1x+5.5 | | 12=z+12 | | 9.7*47= | | T-5-8=11 | | 9u-16=2 | | 11v-8v=6 | | 9m+3=24-6-4m | | 5x=(-6x-9) | | 10.8n-9.8n-5.1=-5.2+16 | | 2x=x-22 | | 6.3x=1 | | a-5+4=15 | | 5c+7=4 | | 18y-17y=-17+7 | | ((144/(37-(102/3)))-17))-25 | | 5+4=15 | | 7(3+t)-2(t+2)= |

Equations solver categories